Effect of Activator on Levels of C, N, P and K Compost of Salak Sidimpuan Leaf Midrib - Amnah, Rizky; Friska, Meiliana (Jurnal Online Pertanian Tropik, 2019)
Salak Sidimpuan leaf midrib is abundant pruning waste. Salak Sidimpuan leaf midrib can be composted containing a number of nutrients (carbon, Nitrogen, phosphorus, and potassium) for plant growth. To speed up the process of composting of salak leaf midrib can be done by giving a number of activators. This study aims to see the effect of activator on the level of elements C, N, P and K compost of salak Sidimpuan leaf midribs. This study used a one-factor randomized block design with 4 levels of treatment of activator, K0 = control, K1 = chopped midribs+cow manure fertilizer, K2 = chopped midribs+EM4, K3 = chopped midribs+cow manure fertilizer+EM4) with three replications. Data were analyzed with ANOVA and continued with DMRT test at 5% level if the F test showed a real effect. The results showed that the K2 with treatment chopped salak Sidimpuan leaf midrib and EM4 activator tended to give the best results in reducing the levels of C-organic and C/N ratio as well as increasing total Nitrogen, total phosphorus and total potassium after composting compared to other activator delivery treatments.